Prevalence and Correlates of Geriatric Depression in Urban Family Cohorts: A Cross-Sectional Survey of Elderly Populations in Shimla, Himachal Pradesh - Menang, Clovis (Journal of Contemporary Medical Practice, 2025)
Background: Aging is a life spanning process of growth and development from birth to old age. Getting older can bring many health challenges to the elderly. Depression is the most common disturbance of mood experienced by elderly. The aim of the present study was to evaluate the level of depression among elderly people living with families in a selected urban community. Objective: To assess the various factors associated with depression and level of depression among elderly people and to find out the association between level of depression and various factors associated with depression among elderly people living with families. Methodology: a descriptive study was conducted in a selected urban community in Shimla, Himachal Pradesh over a sample of 200 elderly living with families using Non- Probability Convenient sampling technique through a dichotomous Questionnaire and Modified Geriatric Depression Scale. Results: The findings of the study revealed that the level of depression among elderly included Severe Depression (11%), Mild Depression (38%) and No Depression (51%) The study showed that Age, Gender, Marital Status and level of dependency showed significant association with the level of factors scores while others factors showed non-significant association with the level of scores. Also, the study showed that Age, Marital status, occupational status and Level of dependency showed significant association with the level of depression score while others factors showed non-significant association with the level of depression score.